Lateral Flow Nitrocellulose Membrane For Diagnostic Kit Application: Synthesis, Characterization And Performance Evaluation - Low , Siew Chun (2010)
Lateral flow nitrocellulose (NC) membrane is one of the main requirements in the biomedical field due to its excellent binding capacity, high wetting properties and low background staining. However, there are still many challenges in the method of membrane fabrication in order to synthesise and control the membrane morphologies to fulfil the whole range of the required immunoassay applications, which is the main focus of this research. In this research, lateral flow NC membrane was successfully fabricated via dry phase inversion.